Systematic preclinical evaluation of CD33-directed chimeric antigen receptor T cell immunotherapy for acute myeloid leukemia defines optimized construct design - Haiying Qin; Nirali N Shah; Terry J Fry; Lila Yang; John A Chukinas; Samiksha Tarun; Marie Pouzolles; Christopher D Chien; Lisa M Niswander; Anthony R Welch; Sarah K Tasian; Naomi A Taylor (Journal for ImmunoTherapy of Cancer)
Background Successful development of chimeric antigen receptor (CAR) T cell immunotherapy for children and adults with relapsed/refractory acute myeloid leukemia (AML) is highly desired given their poor clinical prognosis and frequent inability to achieve cure with conventional chemotherapy. Initial experiences with CD19 CAR T cell immunotherapy for patients with B-cell malignancies highlighted the critical impact of intracellular costimulatory domain selection (CD28 vs 4-1BB (CD137)) on CAR T cell expansion and in vivo persistence that may impact clinical outcomes. However, the impact of costimulatory domains on the efficacy of myeloid antigen-directed CAR T cell immunotherapy remains unknown.Methods In this preclinical study, we developed six CAR constructs targeting CD33, a highly expressed and validated AML target, comprised of one of three single-chain variable fragments with CD3ζ and either CD28 or 4-1BB costimulatory domains. We systematically compared the preclinical in vitro and in vivo efficacy of T cells lentivirally transduced with CD33 CAR constructs (CD33CARTs) against human AML.Results We observed potent in vitro cytokine production and cytotoxicity of CD33CARTs incubated with human CD33+ AML cell lines, as well as robust in vivo antileukemia activity in cell line and childhood AML patient-derived xenograft (PDX) models. Gemtuzumab-based CD33CARTs were unexpectedly toxic in vivo in animal models despite observed in vitro anti-leukemia activity. CD28-based CD33CARTs consistently induced more robust inhibition of leukemia proliferation in AML cell line and PDX models than did 4-1BB-based CD33CARTs. A ‘best-in-class’ lintuzumab-CD28/CD3ζ CAR construct was thus selected for clinical translation.Conclusions CD33 is a critical antigen for potential immunotherapeutic targeting in patients with AML. Based on this rigorous preclinical evaluation, our validated clinical grade lintuzumab-CD28/CD3ζ CD33CART immunotherapy is now under evaluation in a first-in-child/first-in-human phase 1 clinical trial for children and adolescents/young adults with relapsed/refractory AML.Trial registration number clinicaltrials.gov; NCT03971799.